2000
DOI: 10.1128/cdli.7.3.422-426.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Five Commercial Enzyme-Linked Immunosorbent Assays for Detection of Antibodies to Bordetella pertussis

Abstract: Measuring antibodies to Bordetella pertussis antigens is mostly done by enzyme-linked immunosorbent assays (ELISAs). We compared the performance of five commercially available ELISA kits with the help of 65 serum specimens which were repetitively tested for evaluation of the kits. The specimens contained 20 paired serum samples from patients with clinical pertussis, 15 samples were from children vaccinated with a diphtheriatetanus-acellular pertussis vaccine, seven specimens were taken from an interlaboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 29 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…While in-house IgG-Ptx ELISAs accurately distinguished WHO reference preparations and gave results comparable to the expected values, commercial kits using mixtures of antigens did not appear to be able to give results that correlated with those obtained with the WHO reference preparations (223). Comparison of the performances of five commercial ELISAs for detection of antibodies to B. pertussis (two using a mixture of Ptx and FHA and three using an unknown coating antigen) with in-house ELISAs measuring IgG and IgA antibodies to Ptx and FHA according to the CBER protocol resulted in the conclusion that these ELISAs needed further improvement and standardization (260). In a study of convalescentphase sera from 41 patients with culture-or PCR-confirmed pertussis and from 65 control patients with other diseases, the discriminative powers of the IgG-Ptx components of three commercial ELISAs and of the in-house IgG-ELISA were practically identical (AUC of ROC curves, 0.92 to 0.93) (261).…”
Section: Serodiagnosis Of Pertussismentioning
confidence: 99%
“…While in-house IgG-Ptx ELISAs accurately distinguished WHO reference preparations and gave results comparable to the expected values, commercial kits using mixtures of antigens did not appear to be able to give results that correlated with those obtained with the WHO reference preparations (223). Comparison of the performances of five commercial ELISAs for detection of antibodies to B. pertussis (two using a mixture of Ptx and FHA and three using an unknown coating antigen) with in-house ELISAs measuring IgG and IgA antibodies to Ptx and FHA according to the CBER protocol resulted in the conclusion that these ELISAs needed further improvement and standardization (260). In a study of convalescentphase sera from 41 patients with culture-or PCR-confirmed pertussis and from 65 control patients with other diseases, the discriminative powers of the IgG-Ptx components of three commercial ELISAs and of the in-house IgG-ELISA were practically identical (AUC of ROC curves, 0.92 to 0.93) (261).…”
Section: Serodiagnosis Of Pertussismentioning
confidence: 99%
“…Obwohl die ELISA-Technik bislang in zahlreichen Studien zur Bestimmung von Antikörpern gegen B. pertussis eingesetzt wurde,sind bis heute keine standardisierten Testmethoden verfügbar. Die Validierung des eingesetzten Tests wurde durch das Institut für Hygiene und Labormedizin,Klinikum Krefeld, vorgenommen [7].…”
Section: Serologische Untersuchungsmethodenunclassified
“…The different ELISAs contained different antigen preparations. It was concluded from this study that the five tested commercial ELISAs needed further improvement and standardization (17).…”
Section: Discussionmentioning
confidence: 99%
“…infection (27). The detection of IgA antibodies against PT and FHA suggests natural infection not immunization, since IgA is rarely if at all detected following immunization (17,21). However, the detection of IgG to PT and FHA is more sensitive than that of IgA, since not all individuals mount a detectable IgA response following infection (22).…”
mentioning
confidence: 99%